Development of Copper Complexes with Diimines and Dipicolinate as Anticancer Cytotoxic Agents - Natalia Alvarez; Analu Rocha; Victoria Collazo; Javier Ellena; Antonio J. Costa-Filho; Alzir A. Batista; Gianella Facchin (MDPI AG, 2023)
Coordination complexes may act as anticancer agents. Among others, the formation of the complex may facilitate the ligand uptake by the cell. Searching for new copper compounds with cytotoxic activity, the complex Cu-dipicolinate was studied as a neutral scaffold to form ternary complexes with diimines. A series of [Cu(dipicolinate)(diimine)] complexes (where diimine: Phenanthroline, phen, 5-NO2-phenanthroline, 4-methyl-phenanthroline, neocuproine, 3,4,7,8-tetramethyl-phenanthroline, tmp, bathophenanthroline, bipyridine, dimethyl-bipyridine, as well as the ligand 2,2-dipyridil-amine, bam) were synthesized and characterized both in the solid state, including a new crystal structure of [Cu2(dipicolinate)2(tmp)2]·7H2O. Their chemistry in aqueous solution was explored by UV/vis spectroscopy, conductivity, cyclic voltammetry, and electron paramagnetic resonance studies. Their DNA binding was analyzed by electronic spectroscopy (determining Kb values), circular dichroism, and viscosity methods. The cytotoxicity of the complexes was assessed on human cancer cell lines MDA-MB-231, MCF-7 (breast, the first triple negative), A549 (lung epithelial) and A2780cis (ovarian, Cisplatin-resistant), and non-tumor cell lines MRC-5 (lung) and MCF-10A (breast). The major species are ternary, in solution and solid state. Complexes are highly cytotoxic as compared to Cisplatin. Complexes containing bam and phen are interesting candidates to study their in vivo activity in triple-negative breast cancer treatment.